The detection of serum-volatile organic compounds in the diagnostics of hepatocellular carcinoma using gas chromatography–ion mobility spectrometry - Shen, Xin; Xie, Chenglin; Zhang, Shijia; Ai, Wen; Yu, Ziran; Ye, Xu (Frontiers in Chemistry, 2025)
Introduction The third most common cause of cancer-related death worldwide is hepatocellular carcinoma (HCC), a malignant liver tumor that usually arises in patients with cirrhosis and chronic liver disease. New biomarkers are required for bidirectional validation of HCC in clinical practice because of its early asymptomatic stage, high mortality rate, and rapid tumor growth, as well as the high rate of false-positive results obtained for the commonly used serum marker alpha-fetoprotein (AFP).MethodsThis study used gas chromatography–ion mobility spectrometry (GC-IMS) combined with chemometrics to analyze the differences in volatile organic compounds (VOCs) in the serum of patients with and without hepatocellular carcinoma (HCC) in order to explore new biomarkers of HCC.ResultsThe GC-IMS analysis detected 31 VOCs in serum, including 8 ketones, 11 aldehydes, 6 alcohols, 2 esters, and 1 furans, many of which differed in content between the controls and the patients with HCC.ConclusionsThe VOCs obtained from the use of these analytical devices can serve as a reference for developing low-cost equipment in the future. Considering its high efficiency and low cost, the detection of volatile organic compounds can be used as an auxiliary means of diagnosis or for mass screening of the population.